2018
DOI: 10.1371/journal.pone.0189671
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of shear wave elastography in liver fibrosis phantoms—Evaluation of five different systems

Abstract: This study aimed to assess and validate the repeatability and agreement of quantitative elastography of novel shear wave methods on four individual tissue-mimicking liver fibrosis phantoms with different known Young’s modulus. We used GE Logiq E9 2D-SWE, Philips iU22 ARFI (pSWE), Samsung TS80A SWE (pSWE), Hitachi Ascendus (SWM) and Transient Elastography (TE). Two individual investigators performed all measurements non-continued and in parallel. The methods were evaluated for inter- and intraobserver variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 25 publications
10
29
0
Order By: Relevance
“…In our study, the mean elastic modulus value determined with SWE showed an increasing trend from ages 6 to 9 years (for both segments V and VI). The same result, that the SWE measurement is significantly associated with age, was found in normal‐weight children (0.06‐18.9 years) when using the IU‐22 ElastPQ system . Another study involving 51 healthy children (from neonates to 15 years) reported that the mean elastic modulus value exhibited an increasing trend with age when using the SL15‐4 linear array transducer .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In our study, the mean elastic modulus value determined with SWE showed an increasing trend from ages 6 to 9 years (for both segments V and VI). The same result, that the SWE measurement is significantly associated with age, was found in normal‐weight children (0.06‐18.9 years) when using the IU‐22 ElastPQ system . Another study involving 51 healthy children (from neonates to 15 years) reported that the mean elastic modulus value exhibited an increasing trend with age when using the SL15‐4 linear array transducer .…”
Section: Discussionsupporting
confidence: 62%
“…The same result, that the SWE measurement is significantly associated with age, was found in normal-weight children (0.06-18.9 years) when using the IU-22 ElastPQ system. 2 Another study involving 51 healthy children (from neonates to 15 years) reported that the mean elastic modulus value exhibited an increasing trend with age when using the SL15-4 linear array transducer. 6 However, the influence of age on liver stiffness is controversial.…”
Section: Discussionmentioning
confidence: 98%
“…US shear waves degrade and distort through heterogeneous media with variable elasticities until they arrive at a target in vivo tissue, but US shear wave attenuation is less likely to occur with the uniform media of in vitro phantoms. In vivo heterogeneity may result in unpredictable and inconsistent acquisition depth results [23]. Therefore, phantom studies may be optimal for evaluating the performance of US elastography in a setting of the most important parameters such as elasticity, lesion size, and acquisition depths are known [21].…”
Section: Discussionmentioning
confidence: 99%
“…First, because this was a phantom study, we could not evaluate clinical conditions that could affect the results of the shear wave elasticity measurements. The US elastography phantoms did not have viscoelastic components like live soft tissues [23]. Without animal or human data, technical limitations may confound our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed index is utilized to filter out unreliable measurements and results in performance improvement of shear wave elastography. Although several sources of system-dependent bias exist for each type of shear wave elastography, a recent phantom study has compared the S-SWE to other novel shear wave methods, demonstrating a similar and excellent inter-and intra-observer repeatability (22). During examination the child was in the prone position, with the feet dangling over the edge of the examination table.…”
Section: Methodsmentioning
confidence: 99%